Meningkatkan Minat Belajar Siswa Melalui Manajemen Kelas Di Tingkat Sekolah Dasar - Suparlan Suparlan (rogram Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2019)
Class management or arrangement in class is a matter that really needs to be noticed by a teacher, because with good classroom management, in the form of setting a table chair, writing board, cabinets, bookshelves, student seating, students will be comfortable in the learning process. Interest in learning is an encouragement or desire in humans to engage in learning, both in school and outside of school management is a process of supervision carried out on all things involved in implementing policies and achieving goals. In general terms, management is the arrangement or arrangement of an activity.